2016
DOI: 10.1155/2016/4193538
|View full text |Cite
|
Sign up to set email alerts
|

The -174G/C Interleukin-6 Gene Promoter Polymorphism as a Genetic Marker of Differences in Therapeutic Response to Methotrexate and Leflunomide in Rheumatoid Arthritis

Abstract: Objective. To evaluate the association of -174G/C IL-6 polymorphism with failure in therapeutic response to methotrexate (MTX) or leflunomide (LEF). This prospective, observational cohort included 96 Mexican-Mestizo patients with moderate or severe rheumatoid arthritis (RA), initiating MTX or LEF, genotyped for IL-6 -174G/C polymorphism by PCR-RFLP. Therapeutic response was strictly defined: only if patients achieved remission or low disease activity (DAS-28 < 3.2). Results. Patients with MTX or LEF had signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…33 In addition, in a study by Ruiz et al the IL-6 −174 GG genotype was associated with a higher risk of failure in therapeutic response to MTX or leflunomide (lef). 34 However, after stratifying patients’ groups in accordance to MTX or lef, a significant association was observed only in patients treated with lef.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…33 In addition, in a study by Ruiz et al the IL-6 −174 GG genotype was associated with a higher risk of failure in therapeutic response to MTX or leflunomide (lef). 34 However, after stratifying patients’ groups in accordance to MTX or lef, a significant association was observed only in patients treated with lef.…”
Section: Discussionmentioning
confidence: 98%
“…However, two groups examined the association of the IL-6 −174 G/C polymorphism with efficacy of the MTX treatment in patients with RA. 33 , 34 Pawlik et al reported significantly worse response to MTX therapy among patients possessing the IL-6 −174 GG genotype. 33 In addition, in a study by Ruiz et al the IL-6 −174 GG genotype was associated with a higher risk of failure in therapeutic response to MTX or leflunomide (lef).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with folylpolyglutamate synthetase (FPGS) rs1544105-AA or -AG and TYMS rs2853539-AA genotype were associated with poor response to methotrexate ( 53 ). An analysis of the -174 (rs1800795) -GC IL-6 gene promoter polymorphism in RA patients revealed that genotype -GG may be associated with a poorer response to methotrexate when compared to genotypes -GC and -CC ( 54 ), which was in disagreement with another study identifying no association between -GG genotype or G allele and risk of therapeutic failure using different measures for defining response to therapy ( 55 ) ( Table 1 ).…”
Section: Csdmardsmentioning
confidence: 96%
“…Rausz et al have found no association of mastocytosis and the IL6-174G/C polymorphism, however, analysis of the IL6R Asp358Ala polymorphism showed that carriers of the AA genotype had a 2.5-fold lower risk of mastocytosis than those with the AC or CC genotypes [ 85 ]. Ruiz-Padilla et al have found that IL-6 -174G/G genotype confers a higher risk of failure in therapeutic response to Lefludomid in Mexicans patients with rheumatoid arthritis [ 82 ].…”
Section: The Polymorphisms Of Selected Cytokine Genes and Skin Diseasmentioning
confidence: 99%